Using the Basic Efficiency Criteria to Estimate the Security of the New Digital Algebraic Generator System (NDAGS) - Abdulwahed, Mithaq Abdulkareem; Al-Shammari, Ayad G. Naser (Iraqi Journal of Science, 2018)
The Multiplicative Cyclic Group has been used to construct a New Digital Algebraic Generator System (NDAGS). This cryptosystem can be classified as a stream cipher cryptosystem. In this paper we will estimate the efficiency and security of the (NDAGS) by using the Basic Efficiency Criteria (BEC). A comparison has made between the some known generators and (NDAGS). The results of applying the BEC and the comparison results proof the high efficiency of the (NDAGS).